Performance Evaluation of Lecturers in Applied Universities in Shaanxi province - Ma, Yan; Khiam Jin Lee (International Journal of Social Sciences and Public Administration, 2025)
The review of literature on performance evaluation system are abundant but empirical study investing how performance evaluation system influencing lecturers’ work efficiency among applied university in China is under-researched. Applied university in China has unique educational goals and characteristics different from other higher institutions such as research-driven universities. This study aims to address literature gaps related to unanswered nuanced and influencing factors on performance evaluation system and lecturers’ work efficiency in applied university using the cases from Shaanxi province, China. Researcher employed qualitative method. Data were mainly collected through semi-structured interviews from 16 informants of applied and research universities from Shaanxi province who have knowledge on performance evaluation system with direct or indirect impact. The background of informants consists of President of applied universities, faculty members, senior administrators, undergraduates, parents and employers. Interview data was transcribed and analysis was complemented with other official documents.  Qualitative research tools such as coding, memoing, constant comparisons, theoretical saturation and content analysis were used to analyze the interview data. Two cycles of coding led to 23 first-level focused codes, and subsequently reduced to nine second-level focused codes which leading to the discovery of three themes. The findings of this study can be reference for holistic understanding on performance evaluation, support interdisciplinary research particularly to the development of more effective, comprehensive, and context-specific performance evaluation systems that enhance the operational performance and societal impact of applied universities and other institutions.